Visual Analysis of Marketplace Sales Data for Strategic Decision Making Using Tableau - Dewi, Ni Luh Putu Trisna Kantina; Nilawati, Ni Ketut Utami; Anandita, Ida Bagus Gede (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
PT Akselerasi Sumber Berkah is a local company engaged in the production and distribution of beauty and health products, under the brand name Beaudelab. This company was established in 2019. PT Akselerasi Sumber Berkah is located in West Denpasar, Bali. In processing sales data, the company uses Microsoft Excel. The weakness of the data or information generated is still in the form of tables that do not display more informative information in the form of graphs, making it difficult for companies to see sales developments and other information in a short time. Therefore, in this study, a sales data visualization using tableau was built to assist companies in processing table data into information in the form of graphs so that it does not take a long time to see the company's sales development. The research method used in this research is the nine steps kimball method. In this research through the stages of analyzing company data, designing a data warehouse, extract transform load process, implementing data visualization, and testing the system. This system was tested using the user acceptance test method and has obtained results with a percentage of 93% or strongly agree so that this sales data visualization is in accordance with the needs of the company. The results of this study are in the form of 3 pages that display company information in the form of graphs to assist in decision making.